SERVICE MARKETING, HARGA PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PADA CV. BUKIT BATU BANGKINANG - Librina Tria Putri; Henrizal Henrizal; Royansyah Putra (Ensiklopedia of Journal, 2023)
This study aims to determine the effect of service marketing and price on the purchase decision of used motorcycles at CV. Bukit Batu Bangkinang. The analysis used in this research is multiple linear regression analysis with 60 respondents. Hypothesis testing is done by f test (simultaneous) and t test (partial). Based on the results of research and data analysis, it can be interpreted that simultaneously service marketing and prices influence the decision to purchase used motorbikes at CV. Bukit Batu Bangkinang. Likewise, the partial test results show that service marketing and prices influence the decision to buy a used motorbike at CV. Bukit Batu Bangkinang. The contribution of the independent variables to the dependent variables is 67.90%, while the remaining 32.10% is determined by variables outside the research.